Pelaksanaan Sekolah Perempuan untuk Memberikan Pemahaman tentang Relationship and Sex Education - Violyn, Cherish Mauretha Mahar; Desyana, Afifah Fitri; Mahendra, Jonanda Wahyu; Argono, Zahrandy Bintang Bhaskara; Aprilia, Vera Arista; Nurlitasari, Amy; Maharani, Deaningma; Nusaibah, Klarisa Afif; Meytasharoh, Vera Putri; Anisa, Clera Agretyas Nur; Mahardhani, Ardhana Januar (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
The existence of the Dewi Songgolangit Women's School in Lembah Village, Babadan District, Ponorogo Regency can provide an alternative solution to the widespread issue of marriage dispensation and married by accident in Ponorogo Regency. From the results of observations and interviews, it is known that Lembah Village is one of the villages that sends many Indonesian Migrant Workers (PMI). The absence of parents, especially mothers, in the development and growth of their daughters is a problem itself that must be resolved. Therefore, the Dewi Songgolangit Women's School implements a Relationship and Sex Education (RSE) curriculum that is adapted to the target age level. This activity was attended by 60 children who were divided into three classes, namely class A for children aged 9 - 12 years with 25 children, class B for children aged 13 - 15 with 20 children, and class C for children aged 16 - 18 years with 15 children. The methods used in this Women's School activity are delivery of material, discussions and presentations. From the results of the activities carried out, indicators of the success of the program can be seen, namely the increase the understanding of Dewi Songgolangit Women's School student by 82.84%